2016
DOI: 10.3329/jbau.v12i2.28681
|View full text |Cite
|
Sign up to set email alerts
|

Relative abundance of stem borer species and natural enemies in rice ecosystem at Madhupur, Tangail, Bangladesh

Abstract: The relative abundance of different stem borer species and their natural enemies with interaction effects were studied at three growth stages of irrigated Boro rice at Madhupur under the district of Tangail, Bangladesh during January to April, 2013. Five stem borer species viz; Yellow stem borer (Scirpophaga incertulas), Pink stem borer (Sesamia inferens), Dark headed stem borer (Chilo polyhcrysus), Stripped stem borer (Chilo suppressalis), White stem borer (Scirpophaga innotata), and nine different natural en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 3 publications
2
6
0
Order By: Relevance
“…The population of the host egg group was directly proportional to the high level of parasitoid parasitation. This was consistent with Rama et al (2013) report finding that the level of parasitoid egg parasitization would increase with an increasing population of the host egg group, as well as Rahaman et al (2014) which states that the highest S. incertulas population is in the puppi es st age, but yi el d l osses due t o S. incertulas attacks could still be compensated because of the ongoing formation of tillers.…”
Section: Parasitic Level Of Parasitoidsupporting
confidence: 91%
“…The population of the host egg group was directly proportional to the high level of parasitoid parasitation. This was consistent with Rama et al (2013) report finding that the level of parasitoid egg parasitization would increase with an increasing population of the host egg group, as well as Rahaman et al (2014) which states that the highest S. incertulas population is in the puppi es st age, but yi el d l osses due t o S. incertulas attacks could still be compensated because of the ongoing formation of tillers.…”
Section: Parasitic Level Of Parasitoidsupporting
confidence: 91%
“…DHB was found to have least occurrence in both the seasons (4.29-7.18%) (Ragini et al 2000). The relative abundance of stem borer species and their natural enemies revealed that, YSB was dominant followed by DHB, PSB, white stem borer and striped stem borer (SSB) (Rahaman et al, 2014). Akhter et al (2015) reported that, YSB and WSB were dominant from mid-March to May and from August to mid-October, while PSB was dominant from September to first week of April which is in line with the present findings of PSB in Rabi.…”
Section: O N L I N E C O P ÿsupporting
confidence: 90%
“…2 and 3). The data subjected to regression analysis 2 confirmed the increased effect of temperature (R = 0.75%), Considering rice stem borer, YSB, PSB, DHB, SSB and WSB have been reported to occur in South -East Asia (Rahaman et al, 2014). Among these, YSB is the widely distributed and predominantly occurring species than other stem borer species in rice ecosystem.…”
Section: Ethical Approval: Not Applicablementioning
confidence: 59%
“…More than 100 species of insects including 20 economic pests are capable of causing notable damage to rice plants [4]. Insect pests continue to pose threat to rice farming since rice plants serve as their host plants [5].…”
Section: Background Of Brown Plant-hoppermentioning
confidence: 99%